2012
DOI: 10.1099/vir.0.039065-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells and Toll-like receptor 7-dependent signalling promote efficient protection of mice against highly virulent influenza A virus

Abstract: Types I and III interferons (IFNs) elicit protective antiviral immune responses during influenza virus infection. Although many cell types can synthesize IFN in response to virus infection, it remains unclear which IFN sources contribute to antiviral protection in vivo. We found that mice carrying functional alleles of the Mx1 influenza virus resistance gene partially lost resistance to infection with a highly pathogenic H7N7 influenza A virus strain if Toll-like receptor 7 (TLR7) signalling was compromised. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Similar results were seen with intranasal HSV-1, with TLR2 knockouts impaired in cytokine production but not impaired in survival or viral clearance, while TLR2/9 double knockouts had worse outcomes than did single knockouts (10). In influenza virus infection, TLR7 alone seems to be required for successful clearance of a primary infection (73), but inflammasome signaling through IL-1R is important for protective immunity (74). MyD88 Ϫ/Ϫ mice are far more susceptible to lymphocytic choriomeningitis virus (LCMV) infection, while TLR7/9 double knockouts and IL-1R knockouts show only partial susceptibility (75,76).…”
Section: Discussionsupporting
confidence: 56%
“…Similar results were seen with intranasal HSV-1, with TLR2 knockouts impaired in cytokine production but not impaired in survival or viral clearance, while TLR2/9 double knockouts had worse outcomes than did single knockouts (10). In influenza virus infection, TLR7 alone seems to be required for successful clearance of a primary infection (73), but inflammasome signaling through IL-1R is important for protective immunity (74). MyD88 Ϫ/Ϫ mice are far more susceptible to lymphocytic choriomeningitis virus (LCMV) infection, while TLR7/9 double knockouts and IL-1R knockouts show only partial susceptibility (75,76).…”
Section: Discussionsupporting
confidence: 56%
“…However, it should be noted that plasmacytoid dendritic cells (pDCs) are also addressed by both LysM-Cre and CD11c-Cre, although at lower frequency than lung macrophages (32). A recent study suggested that pDCs which appeared to sense virus using TLR7 contribute to IFN production at late stages of infections with influenza virus (17). Thus, it seems likely that at least a fraction of the luciferase activity observed in our LysM/ CD11c-Cre reporter mice originated from pDCs.…”
Section: Cd11cmentioning
confidence: 99%
“…In spite of intensive investigations, surprisingly little is known about the cellular origin of type I IFN in influenza virus-infected lungs. Previous studies demonstrated that various cell types, including macrophages, pneumocytes, and dendritic cells, are able to produce IFN after influenza virus infection (14)(15)(16)(17)(18). However, the relative contributions of these cells to IFN production remained unclear.…”
mentioning
confidence: 99%
“…Dual or triple activation of TLR7, TLR8, and/or TLR9 by single-stranded ODNs may, in fact, occur (23). Of interest, plasmacytoid dendritic cells (pDCs) contribute to the protection of the lung against influenza A virus infections, mainly via TLR7 signals (24).…”
mentioning
confidence: 99%